2023
DOI: 10.1021/acsami.2c23129
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Li+ Diffusion via an Engineered Separator to Realize a Homogeneous Lithium Microstructure in Advanced Li-Metal Batteries

Abstract: Lithium metal, the most promising anode material, is receiving increasing interest owing to its high theoretical capacity (3860 mA h g–1) and low negative potential (−3.04 V vs. standard hydrogen electrode). However, the uneven Li dissolution/deposition behavior causes a degraded cycle stability and safety issues, thus seriously restricting the application of Li-metal batteries (LMBs). Separator modification is one of the most versatile and feasible approaches to overcome this problem. In this study, polypropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Compared with other published composite separators, 17,[28][29][30][31][32][33][34][35][36] the PVDF-HFP/SN separator-based cell maintains a durable operation lifespan and high capacity retention, as shown in Fig. 1b and Table S1 (ESI †).…”
Section: Resultsmentioning
confidence: 92%
“…Compared with other published composite separators, 17,[28][29][30][31][32][33][34][35][36] the PVDF-HFP/SN separator-based cell maintains a durable operation lifespan and high capacity retention, as shown in Fig. 1b and Table S1 (ESI †).…”
Section: Resultsmentioning
confidence: 92%
“…Tremendous efforts have been made to restrain the adverse reactions on the Li-metal anode, such as fabrication of favorable host structures, regulation of electrolyte compositions, modification of separator, and so on. Among them, electrolyte engineering to promote the in-situ formation of a stabilized SEI is one of the plausible solutions. Alternatively, the construction of an artificial SEI could be another simple approach. , As a class of porous coordination polymers, metal–organic frameworks (MOFs) have attracted increasing attention in the electrochemical community due to their large surface area, highly ordered structure, and well-developed porosity. For example, Avery et al have demonstrated that MOFs can be used as a cathode additive to mitigate polysulfide shuttle effect in lithium–sulfur (Li–S) batteries for a better cycling performance .…”
Section: Introductionmentioning
confidence: 99%